Character Building in Education: A Proposed Theory for STAI’s Economic Syari’ah Program - Weni Ratnasari (STAI Auliaurrasyidin Tembilahan, 2018)
Character building in education is a program that has been socialized by the government since 2010. Character building can be integrated in teaching and learning process, it means that every subject must be connected with the norm or value and also improving and application with the daily life. So, the value of character not only shows in cognitive aspect, but they must be internalized as a real accomplishment in social life. Education has responsibility on developing human character, by the effort can be done by planting of local or national culture, changing curriculum, teaching and learning, assessment or evaluation, and habits of all the educators. It is important for educators, staff members and school or university counselors, to promote character building to create an optimal learning environment, create a school, college or university culture welcoming of diversity, and provide safety for all. Keywords: , ,